Prevalence of prediabetes by the fasting plasma glucose and HbA1c screening criteria among the children and adolescents of Shenzhen, China - Yang, Chen; Li, Shaohua; Wu, Liangyan; Ding, Zan; Zhou, Hua; Pan, Ying; Yang, Chufu; Lin, Jinjun; Li, Qiang; You, Yingbin; Zhong, Xu; Chen, Yuyuan; et al. (Frontiers in Endocrinology, 2024)
Background Prediabetes is associated with an increased risk of cardiovascular diseases and all-cause mortality. Rare research in China has evaluated the prevalence of prediabetes among children and adolescents using the HbA1c criterion or the combined FPG-or-HbA1c diagnostic criterion, and researchers paid no attention to the distributions of blood glucose in Shenzhen, especially for juveniles. Methods We conducted a school-based cross-sectional study based on the first-year students from 17 primary, middle, and high schools. Prediabetes was defined as FPG of 5.6–6.9 mmol/L or HbA1c of 5.7%–6.4%. The crude and standardized prevalence of prediabetes with 95% confidence interval (95% CI) was estimated. Results A total of 7519 participants, aged 6 to 17 years, were included. For all subjects, the crude prevalence (95% CI) of prediabetes was 1.49% (1.21–1.77), 8.72% (8.08–9.36), and 9.80% (9.13–10.47) by the FPG-only, HbA1c-only, and FPG-or-HbA1c criteria, respectively. Based on the 2010 Shenzhen census population, the standardized prevalence was 1.56% (males 1.85%, females 1.19%), 11.05% (males 11.47%, females 10.53%), and 12.19% (males 13.01%, females 11.15%) by the corresponding criteria. The proportion of prediabetes was higher for males than females, and the prevalence decreased with grade for males but increased for females. The association of BMI and prediabetes was U-shaped curve, indicating higher rates of prediabetes for underweight and obesity people. Conclusion The blood glucose status of children and adolescents in Shenzhen is worrisome, and the early detection and management of prediabetes are imperative.